Pengaruh Jenis Alkohol pada Sintesis Alkil Ester dari CPO melalui Reaksi Transesterifikasi Menggunakan Katalis Heterogen CaO-MgO - Santoso, Aman; Rizky, M; Sumari, Sumari; Wijaya, Anugrah Ricky; Retnosari, Rini; Asrori, Muhammad Roy (Fakultas Teknik, Universitas Brawijaya, 2021)
Low quality CPO can be made alkyl esters by transesterification reaction by alcohol. The type of alcohol that is often used in the transesterification reaction is methanol but is toxic, so we need an alternative type of alcohol. The purpose of this research is the synthesis of alkyl esters from CPO through transesterification reaction using heterogeneous catalyst CaO-MgO with different types of alcohol. This experimental laboratory research through stages:Â CPO refinement, activation of CaO-MgO catalysts,Â synthesis of alkyl esters from CPO with two types alcohol, identification of the components of the synthesis compound of the synthesized alkyl ester mixture using GC-MS. The results showed that (1) alkyl esters can be synthesized from CPO through the transesterification reaction with methanol and CaO-MgO catalysts with a yield of 85.72%, while the transformation of ethanol is difficult to form ethyl ether (2) the character of methyl ester synthesized has a density 0.86 g / mL, viscosity 3.23 cSt, refractive index 1.44819, and acid number 0.747 mg KOH / g methyl ester, (3) the main component of the synthesized alkyl ester contains 1,200% methyl myristic compound, methyl palmitate 40,637% methyl linoleate 9.332%, methyl 7-octadecenoate 42.986%, and methyl stearate 4.427%.